2021
DOI: 10.1055/s-0041-1730030
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Clinical Decision Support to Reduce Sedative-Hypnotic Prescribing in Older Adults

Abstract: Objective We sought to characterize the performance of inpatient and outpatient computerized clinical decision support (CDS) alerts aimed at reducing inappropriate benzodiazepine and nonbenzodiazepine sedative medication prescribing in older adults 18 months after implementation. Methods We reviewed the performance of two CDS alerts in the outpatient and inpatient settings in 2019. To examine the alerts' effectiveness, we analyzed metrics including overall alert adherence, provider-level adherence, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…After the removal of 110 duplicates and the exclusion of 276 articles following title and abstract screening, a total of 153 full texts were read. In compliance with the inclusion and exclusion criteria, 31 articles reporting quantitative and qualitative parameters 13 33 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 and 29 articles reporting exclusively qualitative parameters of alert acceptance 1 6 12 17 32 68 69 70 71 72 73 74 75 76 77 78 79 80 81 82 83 84 85 86 87 88 89 90 91 were included in the analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After the removal of 110 duplicates and the exclusion of 276 articles following title and abstract screening, a total of 153 full texts were read. In compliance with the inclusion and exclusion criteria, 31 articles reporting quantitative and qualitative parameters 13 33 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 and 29 articles reporting exclusively qualitative parameters of alert acceptance 1 6 12 17 32 68 69 70 71 72 73 74 75 76 77 78 79 80 81 82 83 84 85 86 87 88 89 90 91 were included in the analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Patient characteristics such as the surroundings in which the patient was treated can influence alert acceptance whereas alerts in the in-patient setting were more frequently accepted than in the outpatient setting. 33,67 Furthermore, one study reported that alerts were more often accepted if they concerned male patients. 57 However, this result remained unconfirmed in other studies 54 and might be influenced by other factors not assessed in this study.…”
Section: Discussionmentioning
confidence: 99%
“… 18 This confirms the finding of Joglekar et al that suggests postimplementation evaluation of alerts, including qualitative review of free-text override responses, can contribute to the construction of better triggers that minimize unnecessary prompts that can contribute to alert fatigue. 10 Additionally, clinicians would have been spared the CDS alert in the study of overtesting of older adults if relevant diagnoses were entered into the patient problem or encounter diagnosis list because the diagnoses of a past prostate cancer history or specific urinary symptoms would have suppressed the alert. It is possible these instances will appear less often as clinicians learn from previous exposures that doing so saves them from interacting with CDS alerts.…”
Section: Discussionmentioning
confidence: 99%
“…9 Joglekar and colleagues have described a review of reasons for alert override when the justification was optional and not visible to others. 10 However, we are not aware of other studies that have reviewed visible free-text accountable justifications entered during clinical encounters in outpatient primary care to qualitatively describe what content clinicians enter.…”
Section: Background and Significancementioning
confidence: 99%
“…( 2 , 11 , 12 ) Unlike benzodiazepines and antipsychotics, quality improvement work aimed at reducing potentially inappropriate prescribing of these alternative psychotropic medications has been limited. ( 13 – 15 ) This is important because there is growing evidence describing the risk of falls and fractures in older adults dispensed trazodone and nonbenzodiazepine sedative hypnotics (e.g., zopiclone). ( 16 18 ) Further, trazodone is associated with a similar risk of harm from injurious falls or fractures as benzodiazepines and atypical antipsychotics.…”
Section: Introductionmentioning
confidence: 99%